RELIGIOSITY AND ETHICAL DECISION-MAKING IN ISLAMIC FINANCE: EVIDENCE FROM ACEH - Hendri Mauliansyah; Sharihan Bin Shahidan (GLOBAL RESEARCH IN ECONOMICS AND ADVANCE THEORY (GREAT), 2025)
This study explores how religiosity operates as a behavioral and moral foundation for ethical decision-making in Islamic finance within the distinctive socio-legal context of Aceh, Indonesia. Unlike prior studies that conceptualize ethical conduct primarily as an outcome of formal Shariah compliance, this research adopts an interpretive perspective to examine how religious values are internalized, negotiated, and enacted in everyday financial practices. Drawing on qualitative data from in-depth interviews and focus group discussions with Islamic finance practitioners, Shariah scholars, community leaders, and small business actors, the study employs thematic analysis to uncover the moral logics underlying ethical financial behavior. The findings demonstrate that religiosity functions not merely as an individual attribute but as a socially embedded moral framework shaped by communal norms, institutional trust, and local regulatory arrangements. Participants consistently framed ethical financial decisions as religious obligations rooted in accountability to God, while simultaneously navigating tensions between Shariah ideals and market-based economic pressures. These tensions were particularly salient among small business actors who confronted practical constraints in maintaining Shariah compliance while pursuing financial sustainability. The study further reveals that ethical decision-making is mediated by financial literacy and perceptions of institutional credibility, suggesting that religiosity alone is insufficient without supportive educational and organizational structures. This research contributes to qualitative and critical scholarship in Islamic finance and business ethics by advancing a contextualized understanding of religiosity as a relational and practice-based phenomenon. The findings highlight the importance of integrating ethical education, community engagement, and institutional governance to strengthen ethical integrity and long-term sustainability in Islamic financial systems.